2020
DOI: 10.1101/2020.07.22.20159525
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative Evaluation of 19 Reverse Transcription Loop-Mediated Isothermal Amplification Assays for Detection of SARS-CoV-2

Abstract: Coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 has caused a global pandemics. To facilitate the detection of SARS-CoV-2 infection, various RT-LAMP assays using 19 sets of primers had been developed, but never been compared. We performed comparative evaluation of the 19 sets of primers using 4 RNA standards and 29 clinical samples from COVID-19 patients. Six of 15 sets of primers were firstly identified to have faster amplification when tested with four RNA standards, and were further subjected to par… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…It is revealed that three samples out of 28 did not match with the results of the commercial kits (Supplementary Table S1 ). In both assays, either commercial or the current one, it is estimated that the Ct score of those negative samples was higher than > 37.01 which is out of the WHO recommendation 36 . Therefore, in the current mCoV-2 assay, they are called as negative.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is revealed that three samples out of 28 did not match with the results of the commercial kits (Supplementary Table S1 ). In both assays, either commercial or the current one, it is estimated that the Ct score of those negative samples was higher than > 37.01 which is out of the WHO recommendation 36 . Therefore, in the current mCoV-2 assay, they are called as negative.…”
Section: Discussionmentioning
confidence: 88%
“…The RNA concentration was determined by Nanodrop 2000 (Thermo Fisher Scientific, USA) and the copy number was determined according to the following formula 35 , 36 : …”
Section: Methodsmentioning
confidence: 99%
“…3 Because it does not require a thermocycler, the LAMP process lends itself to both scale-up and miniaturization and can be combined with increasingly sophisticated technology and downstream refinements, including sequencing. Numerous reports of LAMP-based assays for SARS-CoV-2 detection in clinical samples are available, [8][9][10] providing information and encouragement for the development of LAMP-based assays for SARS-CoV-2 in raw sewage.…”
Section: Introductionmentioning
confidence: 99%
“…One of three isothermal amplification technologies currently available in the United States for at-home detection of SARS-CoV-2 utilizes reverse transcription RPA (RT-RPA), and has been shown to detect the virus in nasal swab specimens with as low as twenty genome copies (31, 32). Given their robust sensitivity and specificity, RT-RPA assays are optimized to detect SARS-CoV-2 during the peak period of transmission in individuals with pre-symptomatic, symptomatic, and/or asymptomatic infections (28, 33, 34).…”
Section: Introductionmentioning
confidence: 99%